Impact of Menopausal Hormonal Changes on Bone Health, Orthopedic, Gynecological, and Medical Perspectives. A Cross-Sectional Clinical Study - Sheeba Khan, Muhammad Faheem Kausar, Abdul Waheed, Tauseef Raza, Aaisha Qadir, Nazish Jamil (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Menopause is characterized by a decline in estrogen levels and a host of systemic changes beyond reproductive function. The decrease in estradiol plays a crucial role in altering bone metabolism by accelerating bone resorption and reducing bone mineral density, thereby increasing the risk of osteoporosis. Aims: This cross-sectional clinical study aimed to determine the hormonal changes and associated alterations in bone turnover in postmenopausal women. Methods: A total of n=200 postmenopausal women (mean age 59.8 ± 7.5 years; mean BMI 27.3 ± 4.2 kg/m²) who experienced natural menopause for an average of 10 years were enrolled. Women with a history of hormone replacement therapy or metabolic bone disorders were excluded. Standardized assays were used to measure serum estradiol, follicle-stimulating hormone (FSH), and luteinizing hormone (LH). Bone turnover was assessed by quantifying C-terminal telopeptide (CTX) and osteocalcin, while bone mineral density was measured using dual-energy X-ray absorptiometry. Results: The study found a marked reduction in estradiol levels (15 ± 5 pg/mL) and significant increases in FSH (75 ± 15 mIU/mL) and LH (45 ± 10 mIU/mL). Elevated CTX levels (0.40 ± 0.10 ng/mL) indicated increased bone resorption, and higher osteocalcin levels (25 ± 8 ng/mL) confirmed ongoing bone formation. An inverse correlation between estradiol and CTX underscored the detrimental effect of estrogen deficiency on bone health. Conclusion: The imbalance in bone remodeling during menopause—driven by reduced estradiol and elevated gonadotropins—contributes to decreased bone mineral density and an increased risk of osteoporosis and fractures. Future longitudinal studies should evaluate early intervention strategies and further investigate additional factors affecting bone health. Keywords: Menopause, Estradiol, FSH, LH, CTX, Osteocalcin, Bone Resorption, Osteoporosis, Bone Mineral Density.